Wavelet approximated texture data watershed transform (WATDWT) segmentation of Bio-Medical Images - Ranjan, Pranshu; Rauf Khan, Pervez (International Journal of Computer Sciences and Engineering, 2025)
Extraction of features from the biomedical image using the texture and color space based image processing analysis algorithm is developed using hybrid of DWT, entropy filtering and watershed transform is discussed in this article. To extract the textures we have used entropy features using function on the MATLAB algorithm where it corresponds to the input image parameter with the use of spatial based parameters. The texture analysis based skin texture extraction algorithm consists of steps related to decomposing the input image into a set of binary images from which the color space dimensions of the resulting regions can be computed in order to describe segmented texture patterns.